Drawing lines in the sand: even skipped et al. and parasegment boundaries - Jaynes, James B. (2004)
The pair-rule segmentation gene even skipped (eve) is required to activate engrailed stripes and to organize odd-numbered parasegments (PSs). The protein product Eve has been shown to be an active repressor of transcription, and recent models for Eve function suggest that activation of engrailed is indirect, but these models have not been fully tested. Here we identify the forkhead domain transcription factor Sloppy-paired as the key intermediate in the initial activation of engrailed by Eve in odd-numbered parasegments. We also analyze the roles of the transcription factors Runt and Odd-skipped in this process. Detailed analysis of engrailed and pair-rule gene expression in various mutant combinations shows how eve activates engrailed by repressing these engrailed repressors, and further indicates that mutual repression among pair-rule genes plays an important role in establishing parasegment boundaries. We present a new model of pair-rule gene function that explains the response of these boundaries to the relative levels of Eve and Fushi Tarazu.